Aspects of Cardio protection of Patients with Chronic Heart Failure, as a Consequence of Myocardial Infarction (Eurasian Journal of Learning and Academic Teaching, 2023)
The purpose to study the effect of the myocardoprotector trimetazidine in patients with myocardial infarction complicated by chronic heart failure.